Occurrence of adventitious sprouting in short-lived monocarpic herbs: a field study of 22 weedy species - Malíková, Lenka; Šmilauer, Petr; Klimešová, Jitka (Annals of botany, 2010)
BACKGROUND AND AIMS: Adventitious sprouting from the hypocotyle and roots in monocarpic herbs has been confirmed in previous experimental studies as a means to avoid bud limitation after severe injury in annual and biennial plants. Data regarding the role of adventitious sprouting in natural populations, however, were lacking. The aim of the present study was to assess whether adventitious sprouting occurs in natural populations and how it is affected by plant size, plant injury, plant cover and environmental characteristics. METHODS: Data were sampled from 14 037 individual plants from 389 populations belonging to 22 annual and biennial species. Growth parameters were measured in individual plants, species composition and plant cover in communities were evaluated, and environmental characteristics were estimated using Ellenberg indicator values. KEY RESULTS: It was confirmed that adventitious sprouting occurs in natural populations of all but five species examined. Adventitious sprouting was positively affected by plant size and plant injury. Environmental factors including availability of soil nitrogen were not shown to affect adventitious sprouting. Annual and biennial plants did not differ in sprouting, but upright annuals had a lower number of and longer adventitious shoots than prostrate annuals. CONCLUSIONS: Adventitious bud formation is used to overcome meristem limitation when stem parts are lost due to injury, and thus resprouting in short-lived monocarps should not be overlooked.
Keywords: dusík; Biodiversity; Environment; výhonky rostlin; kořeny rostlin; Hypocotyl; Plant Roots; transpirace rostlin; Plant Shoots; Plant Transpiration; biodiverzita; hypokotyl; životní prostředí; půda; Nitrogen; Soil